2020
DOI: 10.1007/s00428-020-02884-8
|View full text |Cite
|
Sign up to set email alerts
|

Can low autopsy rates be increased? Yes, we can! Should postmortem examinations in oncology be performed? Yes, we should! A postmortem analysis of oncological cases

Abstract: Ever declining autopsy rates have been a concern of pathologists as well as clinicians for decades. Notably, in the field of oncology, data on autopsies and discrepancies between clinical and autoptic diagnoses are particularly scarce. In this retrospective study, we show the effect of a simple catalog of measures consisting of a different approach to obtain consent for autopsy, structured conferencing, and systematic teaching of residents, as well as a close collaboration between clinicians and pathologists o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 23 publications
3
16
0
Order By: Relevance
“…The rate of major discrepancies (37%) in our study was within reported range for oncologic patients ( 14 , 30 33 ). Moreover, in the observed years, a high rate in autopsy did not necessarily correlate with a low rate in major discrepancies, as reported in a large review ( 1 ).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The rate of major discrepancies (37%) in our study was within reported range for oncologic patients ( 14 , 30 33 ). Moreover, in the observed years, a high rate in autopsy did not necessarily correlate with a low rate in major discrepancies, as reported in a large review ( 1 ).…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, in the observed years, a high rate in autopsy did not necessarily correlate with a low rate in major discrepancies, as reported in a large review ( 1 ). This missing correlation was also described by Waidhauser et al ( 30 ). One reason may be the small sample size and short period of our and their study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Given the high numbers of critically ill patients, it became necessary to establish an effective approach to investigate all the aspects of this new disease. Autopsy rates declined dramatically over the last decades, but it can offer the opportunity to directly inspect all organs, identify the cause of death, and generate specimens for further investigations [4]. And this is true for COVID-19 as well, a new disease still not yet understood in detail and lack of sufficient therapeutic approach.…”
Section: Introductionmentioning
confidence: 99%
“…Reports show autopsy rates in Germany, France, Sweden, and the United States have declined by 30% or more since 2005. 10 To help programs mitigate concerns about meeting the required autopsy number during pathology residency, ACGME permits two residents to share an autopsy. 8 While this sanction aids in making the autopsy requirement more attainable for residents, concerns amplified during the COVID-19 pandemic.…”
Section: -3mentioning
confidence: 99%